Diagramming Word Problems: A Strategic Approach for Instruction. (May 2015) - van Garderen, Delinda; Scheuermann, Amy M.
While often recommended as a strategy to use in order to solve word problems, drawing a diagram is a complex process that requires a good depth of understanding. Many middle school students with learning disabilities (LD) often struggle to use diagrams in an effective and efficient manner. This article presents information for teaching middle school students with LD about diagrams and how to use them to solve word problems.